1999
DOI: 10.1038/sj.ijo.0800823
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of geographical variations in body mass index (BMI) and obesity in Spain

Abstract: OBJECTIVE: To identify the factors associated with geographic variations in Body Mass Index (BMI) and obesity in Spain. DESIGN: Cross-sectional, ecological analysis using data on illiteracy rate (per 1000 population), energy intake (kcala apersona ad), sedentary population (%), smoking population (%), alcohol consumption (gapersonad), and percentage of population aged 65 y or over, for Spain's 50 provinces. SUBJECTS: Non-institutionalized population aged 16 y or over. MEASUREMENTS: Median BMI and percentage of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 30 publications
3
22
0
1
Order By: Relevance
“…35 In Spain, however, total energy intake has not been shown to have any effect on regional differences in the prevalence of obesity in a recent ecological study. 16 These data, together with other evidence available at the individual level, make one doubt the in¯uence of energy intake on obesity at the population level, although recent studies that use more precise methods than self reports to measure energy consumption show a clear association between energy intake and weight. For this reason it has been suggested that the inconsistency of this association in epidemiological studies is related to the validity of the instruments that measure the consumption of food in the population since these instruments have been shown to underestimate intake, especially in persons with greater relative weight.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…35 In Spain, however, total energy intake has not been shown to have any effect on regional differences in the prevalence of obesity in a recent ecological study. 16 These data, together with other evidence available at the individual level, make one doubt the in¯uence of energy intake on obesity at the population level, although recent studies that use more precise methods than self reports to measure energy consumption show a clear association between energy intake and weight. For this reason it has been suggested that the inconsistency of this association in epidemiological studies is related to the validity of the instruments that measure the consumption of food in the population since these instruments have been shown to underestimate intake, especially in persons with greater relative weight.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 Likewise, regional differences in body mass index (BMI) and in the prevalence of obesity have been shown in Spain. 16 Some of these variations suggest that there is a potential for the reduction of the magnitude of the problem through public health intervention programs directed both to the general population and to the groups most affected.…”
Section: Introductionmentioning
confidence: 99%
“…However, the factors that contribute to creating this gap remain unclear. Finally, we have identified two studies that, in a similar vein to ours, examine within-country differences in obesity: between two regions in Denmark (Halkjaer and Sørensen, 2004) and across Spanish regions (Gutierrez-Fisac et al, 1999). The evidence drawn from these studies suggests that differences are mainly attributable to educational level and intelligence test scores.…”
Section: Italy Spainmentioning
confidence: 99%
“…The role of diet and physical activity in regional differences in the prevalence of obesity is not convincing (Reeder et al, 1997;Gutíerrez-Fisac et al, 1999). Comstock and co-workers found that obese subjects were less likely to move away from a defined area than lean subjects (Comstock et al, 1966), which may contribute to such regional differences.…”
Section: Introductionmentioning
confidence: 95%